PERBEDAAN LAPORAN KEUANGAN KOPERASI SEBELUM DAN SESUDAH PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK-ETAP) DAN DAMPAKNYA PADA LABA RUGI KOPERASI (Studi Kasus Pada Koperasi Mahasiswa Di Wilayah Kota Malang) - Nariswari, Dian (Jurnal Riset Mahasiswa Akuntansi, 2014)
PSAK No. 27 and SAK ETAP is an important standard that is used in carrying out the functions and activities of the cooperative. This study aims to determine how differences in the cooperative financial statements before and after the application of Financial Accounting Standards Entities Without Public Accountability (SAK-ETAP) and its impact on the income of the cooperative. Sample Student Cooperative research is in the area of Malang serving the financial statements prior to the application of SAK-ETAP in 2009-2010 and after the application of SAK-ETAP 2011-2012. Data collection methods are interviews and documentation. This type of research uses quantitative data Student Cooperative's financial statements. Analysis using statistical methods paired t-test. The results showed that there were significant differences in the financial statements before and after the application of SAK-ETAP. There are some changes to the treatment of assets, liabilities, equity, revenues and expenses of PSAK No. 27 to SAK-ETAP to have an impact on the income of the cooperative. Amendment standards of PSAK No. 27 to SAK-ETAP there are different standards so that any change has an impact on the income of the cooperative. It is expected to further research Student Cooperative studied not only the students who were in the city of Malang that information obtained related to the adoption of PSAK No. 27 and SAK-ETAP not only comparable in Malang region alone but can be compared with the Student Cooperative outside Malang region.